THE EFFECT OF HEDONIC SHOPPING MOTIVATION AND SHOPPING LIFESTYLE ON IMPULSE BUYING ON THE ZALORA ONLINE SHOP - Astuti, Rini; Arsha, Shaka Abiyyu (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to determine and analyze the Influence of Hedonic Shopping Lifestyle on Impulse Buying at Zalora Online Shop (Case Study of Private Higher Education Students in Medan City directly or indirectly. The approach used in this study is a quantitative approach that is associative. The population in this study were students of private tertiary institutions in Medan City that is Medan Area Universities, Panca Budi Universities, and Pelita Harapan Universities The sample in this study used a saturated sample method, amounting to 91 students of private universities in Medan City. The data collection technique in this study used a quantitative approach, used statistical analysis using Classical Assumptions Test, Multiple Linear Regression, Hypothesis Testing, Partial Testing, Simultaneous Testing, and Determinant Coefficient The results of this study prove that directly Hedonic Shopping Motivation and Shopping Lifestyle have a significant effect on Impulse Buying and indirectly Hedonic Shopping Motivation and Shopping Lifestyle have a significant effect on Impulse Buying among Private Higher Education Students in Medan City.